Comparison of Hearing Preservation Outcomes Using Extended Versus Single-Dose Steroid Therapy in Cochlear Implantation. Issue 4 (April 2020) - Gotamco, Giselle L.; Chou, Yi-Fan; Sun, Chuan-Hung; Hsu, Chuan-Jen; Chen, Peir-Rong; Wu, Hung-Pin
Abstract : Objectives: The purpose of this study was to compare the hearing preservation outcomes of patients who received extended versus single-dose steroid therapy in cochlear implant surgery. Design: Case–control. Setting: Tertiary referral centers in Taiwan from April 2017 to 2019. Participants: A total of 70 patients aged 1 to 78 years old (mean = 18.04, standard deviation [SD] = 21.51) who received cochlear implantation via the round window approach were included in the study. Prospectively, 35 cases were enrolled for cochlear implantation with single-dose therapy. Thirty-five controls who underwent cochlear implantation with extended therapy were retrospectively enrolled after frequency matching. Outcome Measures: The main outcome measure was the rate of hearing preservation. This was calculated based on the HEARRING Network formula and results were categorized as complete, partial, and minimal. Impedances served as secondary outcomes. Results: There was no significant difference in the complete hearing preservation rates between the extended and single-dose groups at 6 months postoperatively. Impedances were significantly lower in the extended group after 1 month and 6 months of follow up. When the complete and partial hearing preservation groups were compared, the size of round window opening and speed of insertion were found to be statistically significant. Conclusions: Both extended and single-dose therapies result in good hearing preservation in patients who undergo cochlear implantation. However, better impedances can be expected from patients who received extended therapy. A slower speed of insertion and a widely opened round window play a role in hearing preservation.